Ground-state stabilization of quantum finite-level systems by dissipation. (March 2016) - Pan, Yu; Ugrinovskii, Valery; James, Matthew R.
Abstract: Control by dissipation, or environment engineering, constitutes an important methodology within quantum coherent control which was proposed to improve the robustness and scalability of quantum control systems. The system–environment coupling, often considered to be detrimental to quantum coherence, also provides the means to steer the system to desired states. This paper aims to develop the theory for engineering of the dissipation, based on a ground-state Lyapunov stability analysis of open quantum systems via a Heisenberg-picture approach. In particular, Lyapunov stability conditions expressed as operator inequalities allow a purely algebraic treatment of the environment engineering problem, which facilitates the integration of quantum components into a large-scale quantum system and draws an explicit connection to the classical theory of vector Lyapunov functions and decomposition–aggregation methods for control of complex systems. This leads to tractable algebraic conditions concerning the ground-state stability and scalability of quantum systems. The implications of the results in relation to dissipative quantum computing and state engineering are also discussed in this paper.